Effects of exposure to low-dose ionizing radiation on changing platelets: a prospective cohort study - Ning Liu; Yang Peng; Xinguang Zhong; Zheng Ma; Suiping He; Ying Li; Wencui Zhang; Zijun Gong; Zhenjiang Yao (Komiyama Printing Co. Ltd, 2021)
Abstract Background Numerous studies have concentrated on high-dose radiation exposed accidentally or through therapy, and few involve low-dose occupational exposure, to investigate the correlation between low-dose ionizing radiation and changing hematological parameters among medical workers. Methods Using a prospective cohort study design, we collected health examination reports and personal dose monitoring data from medical workers and used Poisson regression and restricted cubic spline models to assess the correlation between changing hematological parameters and cumulative radiation dose and determine the dose-response relationship. Results We observed that changing platelet of 1265 medical workers followed up was statistically different among the cumulative dose groups (P = 0.010). Although the linear trend tested was not statistically significant (P trend = 0.258), the non-linear trend tested was statistically significant (P non-linear = 0.007). Overall, there was a correlation between changing platelets and cumulative radiation dose (a change of βa 0.008 × 109/L during biennially after adjusting for gender, age at baseline, service at baseline, occupation, medical level, and smoking habits; 95% confidence interval [CI] = 0.003,0.014 × 109/L). Moreover, we also found positive first and then negative dose-response relationships between cumulative radiation dose and changing platelets by restricted cubic spline models, while there were negative patterns of the baseline service not less than 10 years (− 0.015 × 109/L, 95% CI = − 0.024, − 0.007 × 109/L) and radiation nurses(− 0.033 × 109/L, 95% CI = − 0.049, − 0.016 × 109/L). Conclusion We concluded that although the exposure dose was below the limit, medical workers exposed to low-dose ionizing radiation for a short period of time might have increased first and then decreased platelets, and there was a dose-response relationship between the cumulative radiation dose and platelets changing.